Occupational safety and health risk perception among medical laboratory workers in Klang Valley - Anuar I.,; Zahedi F.,; Kadir A,; Mokhtar AB, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Risk management strategy at the workplace needs two way interactions between employee and employer. Therefore, study on risk perception among workers based on scientific analysis is needed to gain knowledge and understanding on how workers perceived risk at the workplace in order to design risk management strategies more effectively. Methodology : A cross sectional study was carried out among 628 respondents from 36 medical laboratories in the public and private sector in Klang Valley. Using a self administered questionnaire, respondents were required to perceive risk on 30 hazards which have been identified in the medical laboratory. Each hazard was encoded by using Likert scale 1= not risky, 2= risky but low, 3= moderate risk, 4= high risk and 5= very high risk. Result : Overall, the study showed that working in the medical laboratory was perceived to of moderate risk. When comparing among ethic groups, the Malays had the highest perception of risk (3.07±0.88) as compared with Indians (3.03±0.88) and the Chinese (2.78±0.90). Employee with higher education and position level perceived low level of risk compared to those with lower education and position level. For those working in different types of laboratories, there are significant difference on risk perception, (p=0.001). Employees who work in government sector perceived higher (3.12±0.93) risk compared to workers in private sector (2.85±0.88). In terms of OSH based knowledge, those with higher level of education and position have a high score knowledge on OSH compared to those have lower education and position level. Conclusion : This study showed that risk perception among workers in medical laboratory is influenced by socio-demography factor such race, education level, job position and the laboratory where the respondents are working.